2014
DOI: 10.1167/iovs.14-15373
|View full text |Cite
|
Sign up to set email alerts
|

Laser Speckle and Hydrogen Gas Clearance Measurements of Optic Nerve Circulation in Albino and Pigmented Rabbits With or Without Optic Disc Atrophy

Abstract: Regardless of the presence of fundus pigmentation or ONH atrophy, ONH MBR and ONH CBF were highly correlated, suggesting that MBR in the ONH tissue is usable for interindividual and intergroup comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 18 publications
2
68
0
Order By: Relevance
“…We found that MBR data pooled from the albino and pigmented rabbits, with or without ET-1 treatment in both the intravenous and intravitreal groups, were highly correlated with capillary blood flow (r = 0.87, P < 0.001, n = 45), with no significant intergroup differences (P = 0.138) in the relationship between MBR and capillary blood flow. 55 The demonstration that MBR can be used in interindividual comparisons represents an important advancement, reinforced by our finding that in glaucomatous eyes, MBR decreases significantly in a stage-dependent manner. 8 We also found that MBR was highly correlated with cpRNFLT and Humphrey field analyzer-measured mean deviation.…”
Section: Laser Speckle Flowgraphymentioning
confidence: 88%
See 1 more Smart Citation
“…We found that MBR data pooled from the albino and pigmented rabbits, with or without ET-1 treatment in both the intravenous and intravitreal groups, were highly correlated with capillary blood flow (r = 0.87, P < 0.001, n = 45), with no significant intergroup differences (P = 0.138) in the relationship between MBR and capillary blood flow. 55 The demonstration that MBR can be used in interindividual comparisons represents an important advancement, reinforced by our finding that in glaucomatous eyes, MBR decreases significantly in a stage-dependent manner. 8 We also found that MBR was highly correlated with cpRNFLT and Humphrey field analyzer-measured mean deviation.…”
Section: Laser Speckle Flowgraphymentioning
confidence: 88%
“…We, in addition to another group, have found that the intravitreous and intravenous administration of ET-1 decreases ONH blood flow in rabbits. 55 Furthermore, the intravitreal administration of ET-1 induced the formation of cupping in the ONH. These findings suggest that ET-1-induced decreases in OBF are associated with ONH cupping and that ET-1 may be a key molecule in OBF decreases, along with an inadequate OBF response, in patients with glaucoma.…”
Section: Endothelinmentioning
confidence: 99%
“…LSFG enables non-invasive, patient- and examiner-friendly quantitative estimation of perfusion at the ONH, retina and choroid, simultaneously, in less than 5 seconds. Validation of the technique for the measurement of ONH perfusion has been established by means of direct comparison with the hydrogen gas clearance method [11,12] and the microsphere method. [13] LSFG has helped add to the understanding of perfusion status and its role in the pathophysiology of numerous ocular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our recent studies suggested that absolute MBR values for the ONH correlated with CBF, indicating the quantifiability of these values in the absence of large topographical and color differences in the ONH [31,33] . This condition was probably observed in the present study because we compared MBR values among eyes with myopic ONHs, which have similar topographical and color appearances.…”
Section: Discussionmentioning
confidence: 86%